The River Cottage Year - Fearnley-Whittingstall, Hugh; Photography by Wheeler, Simon (London Hoder & Stoughton, 2005)
In this, the follow-up to his bestselling "River Cottage Cookbook", the author introduces more than 75 recipes and writes about the culinary year on his Dorset smallholding. With all its outdoorsy information, the real focus of the book is indoors, at Hugh's kitchen table.
Keywords: Cooking